In vitro fertilisation: Women’s questions and concerns in a Malaysian online forum - Chiew, Pung Wun; Mohd Jan, Jariah (Universiti Putra Malaysia, 2018)
Studies have shown that infertility may be caused by male factors, female factors, a mixture of both male and female factors, or due to unexplained reasons. Nevertheless, in some societies, infertility is frequently seen as solely a woman’s problem and women with infertility problems are often forced to suffer blame and humiliation in silence. For example, in Malaysia, a barren married woman is looked down upon, has a lower status, and may be divorced from her husband. Infertility becomes a taboo topic and therefore, not much is known about Malaysian women with infertility problems. However, with the anonymity afforded by computer-mediated communication (CMC), these women are now turning to the online medium for help. This study uses the web content analysis method to investigate the inquiries made by Malaysian women over in vitro fertilization (IVF), a type of infertility treatment, in a local online forum. The findings revealed that the questions asked by women in the forum were primarily concerned with seeking information about IVF. Other types of questions asked include opinion-seeking and questions requesting experience-sharing. These women were also found to use various solidarity strategies to support and encourage one another in persevering with their treatment.